PENGARUH GCG DAN CSR TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI - Armi Sulthon Fauzi; Ni Ketut Suransi; - Alamsyah (InFestasi, 2016)
The aim of this research is to test the influence of GCG and CSR on the firm’s value with profitability (ROA) as the moderating variable. This research uses Double Linear Regression Analysis. Causal research method was employed. 45 companies of manufactures in basic and chemical sector were used as the sample for the year 2012 and 2013. GCG as independent variable was represented with independent commissioner and audit committee. CSR variable was analyzed using GRI 4th version in the year 2015. Tobin’s Q model was used to analyze the firm’s value. This research reveals that the GCG, CSR and ROA simultaneously affects the firm’s value. Meanwhile, the CSR variable affects the firm’s value, GCG variable has negative effect on the firm’s value. The ROA does not affect the firm’s value, ROA which interact with CSR resulting negative effect toward the firm’s value. This means that ROA as moderating variable weakens the relation of CSR on the firm’s value. On the other hand, ROA strengthens the relation of GCG on the firm’s value.